Blocking O-Linked GlcNAc Cycling in Drosophila Insulin-producing Cells Perturbs Glucose-Insulin Homeostasis. - Sekine, O.; Love, D.C.; Rubenstein, D.S.; Hanover, J.A. (Journal of Biological Chemistry, 2010)
A dynamic cycle of O-linked GlcNAc (O-GlcNAc) addition and removal is catalyzed by O-GlcNAc transferase and O-GlcNAcase, respectively, in a process that serves as the final step in a nutrient-driven "hexosamine-signaling pathway." Evidence points to a role for O-GlcNAc cycling in diabetes and insulin resistance. We have used Drosophila melanogaster to determine whether O-GlcNAc metabolism plays a role in modulating Drosophila insulin-like peptide (dilp) production and insulin signaling. We employed transgenesis to either overexpress or knock down Drosophila Ogt(sxc) and Oga in insulin-producing cells (IPCs) or fat bodies using the GAL4-UAS system. Knockdown of Ogt decreased Dilp2, Dilp3, and Dilp5 production, with reduced body size and decreased phosphorylation of Akt in vivo. In contrast, knockdown of Oga increased Dilp2, Dilp3, and Dilp5 production, increased body size, and enhanced phosphorylation of Akt in vivo. However, knockdown of either Ogt(sxc) or Oga in the IPCs increased the hemolymph carbohydrate concentration. Furthermore, phosphorylation of Akt stimulated by extraneous insulin in an ex vivo cultured fat body of third instar larvae was diminished in strains subjected to IPC knockdown of Ogt or Oga. Knockdown of O-GlcNAc cycling enzymes in the fat body dramatically reduced neutral lipid stores. These results demonstrate that altered O-GlcNAc cycling in Drosophila IPCs modulates insulin production and influences the insulin responsiveness of peripheral tissues. The observed phenotypes in O-GlcNAc cycling mimic pancreatic ?-cell dysfunction and glucose toxicity related to sustained hyperglycemia in mammals.